PENGARUH FAKTOR INTERNAL DAN EKSTERNAL TERHADAP KEPATUHAN PERAWAT DALAM MELAKSANAKAN STANDAR PROSEDUR OPERASIONAL PEMASANGAN KATETER DI RUMAH SAKIT PKU MUHAMMADIYAH YOGYAKARTA UNIT II - Maria Ulfa; Tantri Sarzuli (JMMR (Jurnal Medicoeticolegal dan Manajemen Rumah Sakit), 2016)
Background: Patient safety is one of quality indicator of hospital service. Hospitals always improve the quality of care and patient safety, such as implementing Standard Operating Procedures (SOP) in any action of nurses to prevent Hospital Acquired Infection (HAIs). A nurse has certain factors that can influence the SOP implementation in their every action. This study is required to determine factors that influence nurses obedience in implementing SOP of catheter installation at PKU Muhammadiyah Yogyakarta Unit II Hospital. Method: This study using the cross-sectional approach which results are presented in analytical descritive. Research subjects are 30 observed nurses, taken from Emergency room, Naim room, Wardah room, Firdaus room and Zaitun room, by proportionate purposive sampling technique; and 97 nurses for questionnaire. Results and Discussion: Nurses who are obedient to implement catheter installation SOP are 73.33% and 26.67% do not comply. Internal factors (gender, age, years of service, level of education, knowledge, attitude) and external factors (work environment, the characteristics of the group and workload) has no effect on nurses compliance (sig. > 0.05). Conclusion: Internal and external factors have no significant effect on the nurses compliance in implementing SOP of catheter installation at PKU Muhammadiyah Yogyakarta Unit II Hospital. Nurses perform catheter properly and accordant to the SOP are 73.33%.